Educational Thought of Kyai Abbas: A Response to the National Awakening and the Struggle for Independence - Darojat, Jajat; Amirudin, Amirudin; Wajdi, Farid; Imadudin, Iim; Hidayat, Amin; Royyani, Mohammad Fathi (QALAMUNA: Jurnal Pendidikan, Sosial, dan Agama, 2023)
In this study, the researcher aims to discuss the adaptation efforts of Kyai Abbas in the world of Education. Kyai Abbas, as the central figure of West Java in the struggle of November 10, 1945, in Surabaya has made a major contribution to the world of educational thought. This is what becomes interesting to discuss. The movement of the independence struggle carried out by Kyai Abbas through education had a great influence on the birth of a cadre of scholars and freedom fighters for the country. Kyai Abbas maintains religious knowledge on the one hand and educates millions of students to defend the homeland. Pesantren became the basis of movement for the fighters in freeing their country from colonization. The approach used in this study is a literature study with inductive analysis. The procedure used in this study was carried out in three stages, namely orientation, exploration, and focused study. However, previous researchers first determine the object of study research by determining the material and formal objects of research. This is done so that research researchers remain focused on the problem under study, namely the problem of educational thinking Kyai Abbas. From the results of the discussion, the researchers managed to reveal the study's findings, that Kyai Abbas managed to make agitation efforts against a condition of colonization through the line of educational thought. Buntet Pesantren Cirebon is not only a place to print ulama cadres but also print fighters for the country that is being colonized. Kyai Abbas built the foundation for Buntet Pesantren by producing alumni with religious knowledge and militancy in defending the homeland.